Structured ionospheric outflow during the Cassini T55–T59 Titan flybys - Edberg, N. J. T. (2011)
During the final three of the five consecutive and similar Cassini Titan flybys T55–T59 we observe a region characterized by high plasma densities (electron densities of 1–8 cm3 ) in the tail/nightside of Titan. This region is observed progressively farther downtail from pass to pass and is interpreted as a plume of ionospheric plasma escaping Titan, which appears steady in both location and time. The ions in this plasma plume are moving in the direction away from Titan and are a mixture of both light and heavy ions with composition revealing that their origin are in Titan’s ionosphere, while the electrons are more isotropically distributed. Magnetic field measurements indicate the presence of a current sheet at the inner edge of this region. We discuss the mechanisms behind this outflow, and suggest that it could be caused by ambipolar diffusion, magnetic moment pumping or dispersive Alfve´n waves.